Deflection and free vibration of symmetrically laminated quasi-isotropic thin rectangular plates for different boundary conditions - Altunsaray, Erkin; Bayer, Ismail (PERGAMON-ELSEVIER SCIENCE LTD, 2013)
In this study maximum deflection and free vibration of quasi-isotropic thin rectangular plates that are clamped or simply supported from four edges were examined. The effects of changes in aspect ratio and orientation angle on the results of statical bending and free vibration problems according to the Classical Lamination Plate Theory were parametrically calculated by utilizing the Galerkin Method and the Least Squares Method among Weighted Residuals Methods. Obtained results were compared with the software package ANSYS that conducts analyses through Finite Elements Method (FEM). It is observed that the Galerkin Method yields reasonable results much more rapidly than FEM. It was determined that the effect of changes in orientation angles and aspect ratios of different combination of plates, which were constituted with the alternative arrangement of the lamination angles, on maximum deflection and fundamental natural frequency values is substantial. It was considered that the optimum plates that will properly satisfy different load conditions on the different parts of the structure can be determined with the use of the nondimensional tables prepared with the Galerkin Method in the preliminary design of composite hulls. It is proposed that savings from materials, labor, testing and time can be achieved by this means. (C) 2012 Elsevier Ltd. All rights reserved,
Keywords: Quasi-isotropic plates; Weighted Residual Methods; The Galerkin Method; The Least Square Method; Classical Lamination Plate Theory; Parametric study; Maximum deflection; Free vibration; Engineering; Oceanography